Unexpected events trigger task-independent signaling in VIP and excitatory neurons of mouse visual cortex - Farzaneh Najafi; Simone Russo; Jérôme Lecoq (iScience)
Summary: The visual cortex predicts incoming sensory stimuli through internal models that are updated following unexpected events. Cortical inhibitory neurons, particularly vasoactive intestinal polypeptide (VIP) interneurons, play a critical role in representing unexpected stimuli. Notably, this response is stimulus non-specific, raising the question of what information it conveys. Given their unique connectivity, we hypothesized that during unexpected stimuli, VIP neurons encode broad context signals, referred to here as task-independent information. To test this hypothesis, we analyzed the Allen Institute Visual Behavior dataset, in which mice viewed repeated familiar images and unexpected omissions of these images, while two-photon calcium imaging was performed from distinct cell types across primary and higher-order visual areas. Using dimensionality reduction methods, we found that, in contrast to image presentations, unexpected omissions trigger task-independent signaling in VIP and excitatory neurons. This signaling may facilitate the integration of contextual and sensory information, enabling updated predictions.